Fabrication and evaluations of PZT thin films by RF reactive sputtering using solid oxygen-source / Sukreen Hana Herman, Kimihiro Sasaki and Tomonobu Hata - Herman, Sukreen Hana; Kimihiro, Sasaki; Tomonobu, Hata (2004)
PZT films were prepared on Pt/Ti/SiO2/Si substrate by RF reactive sputtering apparatus using metal-oxide composite ZrTi+PbO2 powder and pellet targets. The main sputtering conditions are as follows: sputtering gas is argon and oxygen, gas pressure is 1810-2Torr, 02/Ar flow rate is 0% and 4.2%, substrate temperature is 200 (unintentionally heated), 450 and 550°C. PbOz target occupation is 300%. It is confirmed that PbOz pellet target has the potential to be the oxygen-source during the deposition with a high deposition rate. Perovskite PZT peak was observed in XRD measurement for film grown with PbO2 pellet target without introducing, my oxygen gas and with a small target occupation during deposition.